Characteristics and response of mouse bone marrow derived novel low adherent mesenchymal stem cells acquired by quantification of extracellular matrix - Zheng, Ri-Cheng (The Korean Academy of Prosthodontics, 2014)
PURPOSE: The aim of present study was to identify characteristic and response of mouse bone marrow (BM) derived low-adherent bone marrow mesenchymal stem cells (BMMSCs) obtained by quantification of extracellular matrix (ECM). MATERIALS AND METHODS: Non-adherent cells acquired by ECM coated dishes were termed low-adherent BMMSCs and these cells were analyzed by in vitro and in vivo methods, including colony forming unit fibroblast (CFU-f), bromodeoxyuridine (BrdU), multi-potential differentiation, flow cytometry and transplantation into nude mouse to measure the bone formation ability of these low-adherent BMMSCs. Titanium (Ti) discs with machined and anodized surfaces were prepared. Adherent and low-adherent BMMSCs were cultured on the Ti discs for testing their proliferation. RESULTS: The amount of CFU-f cells was significantly higher when non-adherent cells were cultured on ECM coated dishes, which was made by 7 days culturing of adherent BMMSCs. Low-adherent BMMSCs had proliferation and differentiation potential as adherent BMMSCs in vitro. The mean amount bone formation of adherent and low-adherent BMMSCs was also investigated in vivo. There was higher cell proliferation appearance in adherent and low-adherent BMMSCs seeded on anodized Ti discs than machined Ti discs by time. CONCLUSION: Low-adherent BMMSCs acquired by ECM from non-adherent cell populations maintained potential characteristic similar to those of the adherent BMMSCs and therefore could be used effectively as adherent BMMSCs in clinic.